Aspergilloma as a Skull Base Tumor: A Case Report - Sevil Nasirmohtaram; Azin Tabari; Mehdi Zeinalizadeh; Mohammadreza Salehi; Seyed Musa Sadr Hosseini (Caspian Journal of Neurological Sciences)
Background: Aspergillosis is a fungus-related health problem that may include allergic reactions like allergic bronchopulmonary aspergillosis, which presents as upper and lower airway disease or chronic and invasive forms of fungal infection. Case Presentation: Here, we report a young woman with a history of poorly controlled asthma. She was primarily diagnosed with a skull base tumor due to the left eye proptosis and soft tissue mass involving the orbit and skull base, with intracranial extension. The diagnosis of aspergillosis was confirmed after tissue sampling, and the patient was successfully managed with an oral anti-fungal agent. Conclusion: Aspergillosis could be a differential diagnosis in the patients presenting with skull base tumor and a positive history of allergic asthma.